2018
DOI: 10.3389/fphys.2018.00987
|View full text |Cite
|
Sign up to set email alerts
|

BdorOR88a Modulates the Responsiveness to Methyl Eugenol in Mature Males of Bactrocera dorsalis (Hendel)

Abstract: Insect attractants are important prevention tools for managing populations of the Oriental fruit fly, Bactrocera dorsalis (Hendel), which is a highly destructive agricultural pest with health implications in tropical and subtropical countries. Methyl eugenol (ME) is still considered the gold standard of B. dorsalis attractants. Mature male flies use their olfactory system to detect ME, but the molecular mechanism underlying their olfactory detection of ME largely remains unclear. Here, we showed that ME activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 120 publications
1
45
0
Order By: Relevance
“…In B. dorsalis , it is well known that methyl eugenol (ME) is strongly attractive to males [ 14 ]. Based on the high potency and sex pheromone-like behavior of ME, trapping systems have been developed to manage B. dorsalis and as well as additional molecular mechanistic analysis of B. dorsalis- ME interactions [ 15 , 16 ], but primarily with male flies. However, the oviposition by females is the main mechanism of fruit damage by insects.…”
Section: Introductionmentioning
confidence: 99%
“…In B. dorsalis , it is well known that methyl eugenol (ME) is strongly attractive to males [ 14 ]. Based on the high potency and sex pheromone-like behavior of ME, trapping systems have been developed to manage B. dorsalis and as well as additional molecular mechanistic analysis of B. dorsalis- ME interactions [ 15 , 16 ], but primarily with male flies. However, the oviposition by females is the main mechanism of fruit damage by insects.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that these findings support our suggestion that the maxillary palps be an additional focal point of olfactory research in Tephritid fruit flies. This can hopefully be combined with extensive work conducted recently on the transcriptomes of the oriental fruit fly and other Tephritid species focusing on identifying genes and proteins in these species involved in chemoreception ( Zheng et al 2013 ; Wu et al 2015 ; Elfekih et al 2016 ; Liu et al 2016 ; 2017 , 2018 ; Miyazaki et al 2018 ) as part of the search for novel ways to control these highly destructive and invasive pests.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the seminal work of Metcalf and coworkers done over four decades ago describing how B. dorsalis males respond to ME ( Metcalf et al 1975 ), more recent reviews of the literature on B. dorsalis olfaction, especially that pertaining to ME, have focused almost entirely on the role of the antennae ( Zheng et al 2013 ; Wu et al 2016 ; Liu et al 2017 , 2018 ). While it has been established that the ability of these male flies to be attracted to lures such as ME depends on the presence and activation of olfactory receptor neurons in the sensilla of the antenna ( Zheng et al 2012 ; Liu et al 2017 , 2018 ), it is also known that olfactory sensilla also exist in the maxillary palp ( Zhang et al 2011 ). This includes the type of sensilla basiconica earlier described as thin-walled multiporous pitted sensilla ( Dickens et al 1988 ) that are also present in the antenna ( Lee et al 1994 ).…”
mentioning
confidence: 99%
“…ORs are considered to be chemosensory receptors for male attractants in Dacini fruit flies. Indeed, OR88a has been characterized as a candidate ME receptor in B. dorsalis by heterologous expression using Xenopus oocytes, and behavioral bioassays of male flies treated with RNAi-mediated OR88a knockdown [135]. The involvement of the OR system in the chemoreception of ME has also been shown by RNAi-mediated ORCO knockdown in B. dorsalis [134].…”
Section: Future Research 61 Characterization Of Chemosensory Receptmentioning
confidence: 99%
“…Furthermore, RNAi-mediated knockdown of ORCO reduced the attractiveness of ME in the treated males. Most importantly, a recent study characterized OR88a as the ME receptor [ 135 ]. This study showed that the transcriptional level of OR88a was enhanced by exposure to ME, as seen for ORCO .…”
Section: Major Molecular Components In Insect Chemoreceptionmentioning
confidence: 99%